English Vocabulary Teaching Techniques among Pre-Service Teachers for Young Learners in Indonesian Elementary Schools - Atanasius Bria; Ima Widyastuti; Hazel Dorothy Cesar (Universitas Sarjanawiyata Tamansiswa, 2026)
This research discusses the vocabulary teaching approaches conducted by pre-service teachers for young learners in Indonesian primary schools. The use of controlled, semi-controlled, and free activities are discussed in this study. The study was based on the taxonomy of Crookes and Chaudron and was based on twelve video transcripts of genuine classroom teaching. The results show a predominance of controlled techniques, sporadic usage of free techniques – mostly digital and game-based methodology – and minimal semi-controlled approaches. The talk links these tendencies with recent advancements in educational technology and contextual problems in Indonesia, and discusses implications for teacher education, curriculum design and creation of digital resources for young learners’ English lessons.